Co-infection of tuberculosis and hepatitis B virus in HIV patients: Implications for diagnosis and treatment - Dansura, Mangpin L.; Dangana, Amos; Samuel, Bwede E.; Gagari, Villeng F.; Miri, Nanpon; Gyang, Nyiri M.; Adejuyigbe, Zacchaeus; Ugwu, Chinwe N.; Nanbol, Helen D.; Uzoebo, Nkiruka (Trends in Infection and Global Health, 2025)
Hepatitis B virus (HBV) and tuberculosis (TB) infections are common causes of liver cirrhosis and hepatocellular carcinoma. First-line anti-TB medications are known to cause drug-induced liver injury (DILI). The aim of this study was to investigate whether HBV and TB co-infection increases susceptibility to liver failure and poor outcomes during anti-TB treatment in HIV-positive patients. HBV infection was detected using the enzyme-linked immunosorbent assay (ELISA) method, while TB infection was confirmed through Lowenstein-Jensen (LJ) medium culture. The severity and incidence of liver failure and mortality were compared, and risk factors influencing clinical outcomes were identified. Patients were categorized as new TB cases, relapse TB cases, or defaulters. Among the total cases, 64.5% were classified as new, 18% as relapse, and 17.5% as defaulters of TB cases. The prevalence of HBV infection among new, relapse, and defaulter cases was 11.5%, 4.8%, and 1.6%, respectively. In terms of TB classification, the prevalence of HBV infection among patients with pulmonary TB and extrapulmonary TB was 10.6% and 7.1%, respectively, with no cases recorded in the defaulter category. The prevalence of triple infection (HIV-TB-HBV) was found to be 13.3% in new TB cases and 3.3% in relapse TB cases. Patients undergoing anti-TB therapy with chronic HBV co-infection were more susceptible to liver failure and had poorer treatment outcomes. Regular monitoring of liver function is essential, and anti-HBV therapy should be considered for patients with high viral loads before initiating anti-TB treatment.